Hydrodynamics of a bordered collar as a countermeasure against pier scouring. (28th October 2020) - Ferraro, Domenico; Fenocchi, Andrea; Gaudio, Roberto
Abstract : An experimental campaign on long-term clear-water scour at bridge piers with different configurations was performed in a laboratory to investigate the effects of different countermeasures. Tests were performed in a flume with a movable sediment bed for an unprotected cylindrical pier, a cylindrical pier with a standard collar and a cylindrical pier with a bordered collar. The scoured beds at the equilibrium stage were acquired through the photogrammetry technique and the efficiencies of the tested countermeasures were measured. Results showed a reduction in the maximum scour depth as well as in the scour hole volume with respect to the unprotected pier. The maximum scour depth was reduced by 59.63% with the standard collar and by 63.51% with the bordered collar. The scoured volume was reduced by 43.80% with the standard collar and by 60.00% with the bordered collar. The three-dimensional Reynolds-averaged Navier–Stokes equations were solved numerically to reproduce the hydrodynamics of the experiments. The volume of fluid technique was used to reproduce the free surface. For each test, the results of the simulations were analysed to investigate the flow field around the pier both at the initial (flat-bed) and at the equilibrium stages, highlighting the changes in the velocity field owing to the presence of the standard collar and of the bordered collar.